Ecofriendly approaches for management of insect pests of maize in small scale storage - Soujanya, P Lakshmi; Sekhar, J C; Suby, S B; Rakshit, Sujay (Indian Farming, 2020)
Right execution of pre-storage activities will help farmers by reducing the risk of insect pest infestation from field stage to storage. Utilization of botanicals alone and in combination with different packaging materials reduces rice weevil infestation and its associated losses. Also, application of botanicals through novel methods protects the stored grain without any adverse effects. Implementation of preventative measures and appropriate use of botanicals in hermetic storage helps in strengthening food security and higher returns to small scale farmers.